Photo-Fenton and Fenton Oxidation of Recalcitrant Industrial Wastewater Using Nanoscale Zero-Valent Iron. (17th October 2012) - Hansson, Henrik; Kaczala, Fabio; Marques, Marcia; Hogland, William
Abstract : There is a need for the development of on-site wastewater treatment technologies suitable for "dry-process industries, " such as the wood-floor sector. Due to the nature of their activities, these industries generate lower volumes of highly polluted wastewaters after cleaning activities. Advanced oxidation processes such as Fenton and photo-Fenton, are potentially feasible options for treatment of these wastewaters. One of the disadvantages of the Fenton process is the formation of large amounts of ferrous iron sludge, a constraint that might be overcome with the use of nanoscale zero-valent iron (nZVI) powder. Wastewater from a wood-floor industry with initial COD of 4956 mg/L and TOC of 2730 mg/L was treated with dark-Fenton (nZVI/H2 O2 ) and photo-Fenton (nZVI/H2 O2 /UV) applying a 2-level full-factorial experimental design. The highest removal of COD and TOC (80% and 60%, resp.) was achieved using photo-Fenton. The supply of the reactants in more than one dose during the reaction time had significant and positive effects on the treatment efficiency. According to the results, Fenton and mostly photo-Fenton are promising treatment options for these highly recalcitrant wastewaters. Future investigations should focus on optimizing treatment processes and assessing toxic effects that residual pollutants and the nZVI might have. The feasibility of combining advanced oxidation processes with biological treatment is also recommended.